Collective Syntheses of Eight Phorbaketals via Total Synthesis of Phorbaketal A. Issue 12 (2nd November 2022) - Lee, Jaeyeon; Joung, Seewon; Lee, Hee‐Yoon
Abstract: A practical total synthesis of phorbaketal A, a representative natural product among spiroketal containing natural products from marine sponge Phorbas sp . that has been a productive source of structurally diverse terpene natural products with various biological activities was achieved through gold‐catalyzed spiroketalization of the alkynediol precursor accompanied by the epoxide rearrangement to the corresponding allylic alcohol followed by an olefin isomerization. With the solid pathway to produce phorbaketal A in hand, we achieved collective synthesis of eight phorbaketals as they appeared to be derived from phorbaketal A in nature. Abstract : A practical total synthesis of phorbaketal A, which has been a productive source of structurally diverse terpene natural products with various biological activities, was achieved through gold‐catalyzed spiroketalization of the alkynediol precursor accompanied by the epoxide rearrangement to the corresponding allylic alcohol followed by an olefin isomerization.